1999
DOI: 10.1080/00074919912331337597
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of Expenditure Inequalities in Indonesia: 1987, 1990 and 1993

Abstract: This article investigates the contribution of inter-regional disparity to total national inequality in household expenditure, by decomposing national inequality into within- and between-province components. This is done by applying the Theil inequality decomposition technique to household expenditure data from the National Socio-Economic Survey. Whereas inter-provincial disparity accounted for 12-14% of total inequality among urban households and 7-8% among rural households, urban-rural disparity accounted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…Everyday discourse in town is not strongly class-oriented. Indeed, the Gini index of inequality is somewhat lower in Indonesia's trade-, agriculture-and bureaucracy-dominated provinces than in the industrialized cities (Akita and Lukman 1999). The town has an internal spatial structure consisting of business and government quarters, middleclass housing, and lower-class kampungs, not so different from that once described by Wertheim (1959:180-1).…”
Section: Classmentioning
confidence: 87%
“…Everyday discourse in town is not strongly class-oriented. Indeed, the Gini index of inequality is somewhat lower in Indonesia's trade-, agriculture-and bureaucracy-dominated provinces than in the industrialized cities (Akita and Lukman 1999). The town has an internal spatial structure consisting of business and government quarters, middleclass housing, and lower-class kampungs, not so different from that once described by Wertheim (1959:180-1).…”
Section: Classmentioning
confidence: 87%
“…Outer island inequalities -whether measured within urban areas or between urban and rural areas -are actually slightly lower than in Java. This is due to the absence of industry and the dominance of agriculture, trade and bureaucracy in those areas (Akita and Lukman 1999). The neo-patrimonial relations between intermediate class members and their poorer dependents are simply unequal friendships -they exist between people who are not separated from each other by light years on the social spectrum.…”
Section: Social Forcesmentioning
confidence: 99%
“…All of NTT's districts except the city of Kupang are officially classified as regions of extreme poverty (daerah tertinggal), the highest proportion among all the provinces of Indonesia.21 Intra-rural, intra-urban, and between urban-rural inequalities remained relatively high in NTT considering it has no industry (Akita and Lukman 1999). Inequality has a strong spatial component -as urbanization increases, so does inequality.…”
Section: Middle Indonesia Todaymentioning
confidence: 99%
“…Note that the prefectural GDP data for 2000 onward were based on 93SNA, whereas the other data were based on 68SNA. Further, the inflation rate may not be uniform across prefectures, as proposed by Akita and Lukman (1999), who suggested that price adjustment may not only affect the magnitude of inequality indices in any period but may even reverse the trend of inequality. This study relies on these data, and care should be considered while interpreting the results.…”
Section: Datamentioning
confidence: 99%